Karakteristik Campuran AC-BC Yang Menggunakan Batu Sungai Sadang Kecamatan Duampanua Kabupaten Pinrang - Nifre Dirgahayu; Rais Rachman; Alpius (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
Technological developments in the field of civil engineering, especially roads, are growing rapidly along with the times. However, the lack of availability of materials used in construction is a problem that needs to be addressed. Therefore, in this study, we tested the Sadang River stone as an aggregate that could be utilized in the pavement mixture, especially the AC-BC layer by using the marshal test method with reference to the 2018 Bina Marga specification. The results obtained from this study were the stability value of 1190,28 kg. -1545,08 kg, flow 2,35 mm -3,85 mm, VIM 4,335% - 3,098%, VMA 14,64% - 18,26%, VFB 70,39% - 83,03%.